DEVELOPMENT AND PRODUCTION OF CERAMIC TILES FROM WASTE BOTTLE POWDER (MILLED GLASS) - Elakhame, Z. U.; Ifebhor, F.; Asotah, W. A. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
Ceramic tiles were produced from a varying mixture of clay and milled glass and the physio-chemical properties of the samples were determined. 0–70% weight milled glass was added to clay mineral. Seven samples were obtained before the clay which serves as binder was not able to hold the mixture together. It was discovered that the porosity of the tiles increased as the percentage weight of the clay material decreased and milled glass increased. Also, the compressive strength of the tiles peaked at sample 5 (60% clay & 40% milled glass). Results obtained showed that samples containing from 30-60% weight of milled glass in proportion with clay percentage had the best formulation properties. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 50-59